Effect of drought and heat stresses on photosynthesis, pigments, and xanthophyll cycle in alfalfa (Medicago sativa L.) - C. XU; C.G. HE; Y.J. WANG; Y.F. BI; H. JIANG (Photosynthetica, 2020)
Climate changes severely influence photosynthetic activity of plants. Studies on the combined effect of drought and heat stress on photosynthesis, pigments, and xanthophyll cycle particularly in alfalfa (Medicago sativa L.) are limited. Thus, this study investigated the combined effects of drought and heat stress in two alfalfa varieties ('Deqin' and 'Algonguin'). Results revealed that the values of the net photosynthetic rate demonstrated a significantly decreasing tendency under stresses. The effect of stresses on ribulose 1,5-bisphosphate carboxylase activity in both varieties showed a trend of first declining and then rising. Meanwhile, phosphoenolpyruvate carboxylase activity showed an increasing tendency. The intensification of stresses led to reduced photochemical efficiency and increased capability of thermal dissipation. A linear correlation was found between nonphotochemical quenching and xanthophyll cycle components. Thus, the change in carotenoids demonstrated an important role in photoprotection, the xanthophyll cycle was the main way of dissipation of excess energy under stress conditions in alfalfa.